EFFECTS OF INWARD PROCESSING REGIME ON INTERNATIONAL TRADE AND INDUSTRIAL PRODUCTION: AN EMPIRICAL RESEARCH ON TURKEY - Şeker, Ayberk (Kenan ÇELİK, 2021)
The inward processing regime is an incentive system that targets to increase production and export levels in the country or to procure the necessary raw materials at lower costs to increase in production and exports in Turkey. The effects of inward processing regime on industrial production and exports of Turkey is analyzed by using monthly datas between 2012 and 2019 in the scope of this paper. Whereas it is analyzed the long-term relationships between the variables via Gregory-Hansen cointegration test, Granger and frequency domain causality tests are used to examine causality relationships. As a result of the analysis, it has been determined that there is a long-term relationship between inward processing regime, industrial production index and export/import coverage ratio. While there is a bidirectional causality relationship between industrial production index and inward processing regime, it is seen that there is a causal relati-onship from the industrial production index to inward processing regime in the short, medium and long-term; it is observed that there is a causal relationship from inward processing regime to the industrial pro-duction index in the medium and long term. In addition, it has been revealed that there is a unidirectional causality relationship from the inward processing regime to export/import coverage ratio in the short and medium term.

Dâhilde işleme rejimi, Türkiye’de üretim ve ihracat düzeyini arttırmak amacıyla ülke içerisinde bulunmayan veya daha uygun maliyetlerle gerekli hammaddelerin elde edilmesini ve üretim sonucunda ihracatın arttı-rılmasını hedefleyen bir teşvik sistemidir. Çalışma kapsamında Türkiye’de dâhilde işleme rejiminin sanayi üretimi ve ihracat hacmi üzerindeki etkileri, 2012-2019 yılları arasında aylık frekanstaki veriler kullanılarak analiz edilmiştir. Değişkenler arasındaki uzun dönemli ilişkileri değerlendirmek amacıyla Gregory-Hansen eşbütünleşme testi, nedensellik ilişkilerini incelemek için ise Granger ve frekans alanı nedensellik testleri kullanılmıştır. Analizler neticesinde, dâhilde işleme rejimi, sanayi üretim endeksi ve ihracatın ithalatı karşı-lama oranı arasında uzun dönemli bir ilişkinin bulunduğu tespit edilmiştir. Bununla birlikte, sanayi üretim endeksi ve dâhilde işleme rejimi arasında iki yönlü bir nedensellik ilişkisi olup, sanayi üretim endeksinden dâhilde işleme rejimine doğru kısa, orta ve uzun dönemde nedensellik ilişkisi olduğu görülürken; dâhilde işleme rejiminden sanayi üretim endeksine doğru ise orta ve uzun dönemde nedensellik ilişkisinin var oldu-ğu görülmüştür. Ayrıca dâhilde işleme rejiminden ihracatın ithalatı karşılama oranına doğru kısa ve orta dö-nemde tek yönlü bir nedensellik ilişkisi bulunduğu ortaya koyulmuştur.
DAHİLDE İŞLEME REJİMİNİN ULUSLARARASI TİCARET VE SANAYİ ÜRETİMİ ÜZERİNDEKİ ETKİLERİ: TÜRKİYE ÜZERİNE AMPİRİK BİR ARAŞTIRMA